2006
DOI: 10.1002/mrm.21023
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the expression level of integrin receptor αvβ3 in cell lines and MR imaging with antibody‐coated iron oxide particles

Abstract: Targeted imaging requires site-specific accumulation of a contrast agent (CA), and the properties of that agent must be selected according to the abundance of the target to obtain a signal above the detection limit of the instrument. However

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 26 publications
(19 reference statements)
3
41
0
Order By: Relevance
“…Here k u is the carrying capacity of the cancer cell populations and it is taken to be ∼ 6.7 · 10 7 cell/volume, and f m is the maximum ECM density at which the ECM fills up all available physical space and it is taken to be equal to 4 mg/volume, as in Domschke et al (2014). Finally, c m is the maximum integrin density and it is taken to be 5 · 10 4 integrins per cell (as in Benedetto et al (2006)). For the kernels K i (r) , i = 1, 2, we choose (as in Domschke et al (2014)) the dimensionless functionsK i (r) , i = 1, 2, given bỹ…”
Section: Non-dimensionalisation Of the Modelmentioning
confidence: 99%
“…Here k u is the carrying capacity of the cancer cell populations and it is taken to be ∼ 6.7 · 10 7 cell/volume, and f m is the maximum ECM density at which the ECM fills up all available physical space and it is taken to be equal to 4 mg/volume, as in Domschke et al (2014). Finally, c m is the maximum integrin density and it is taken to be 5 · 10 4 integrins per cell (as in Benedetto et al (2006)). For the kernels K i (r) , i = 1, 2, we choose (as in Domschke et al (2014)) the dimensionless functionsK i (r) , i = 1, 2, given bỹ…”
Section: Non-dimensionalisation Of the Modelmentioning
confidence: 99%
“…There is a great deal of interest in enhancing the utility of these tools in medicine and research through the development of molecularly-targeted MRI contrast agents. One example might be a chimeric molecule comprised of a contrast agent tethered to a molecule capable of binding to a specific protein or other biomolecular target with high affinity and specificity [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, we previously reported that a peptide selected from a phage display library to bind the yeast Gal80 protein can be linked to GdDOTA to create a reagent capable of imaging Gal80 protein in vitro [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…To solve equations (29) to (32) 22,26 In one study, a chamber containing tumor cells was implanted into rabbit ears, and FITClabeled particles were then intravenously injected into the contralateral ear. When steady state was achieved, photobleaching was applied for a short period, during which particle diffusion was neglected.…”
Section: Determination Of Parametersmentioning
confidence: 99%
“…Cells were incubated at 4 °C prior to the addition of a nanoparticle solution and during the incubation of the nanoparticle solution to inhibit endocytosis. Assuming 1:1 binding and a constant concentration of free particles, the binding and internalization of particles on a per-cell basis can be described as shown below: (29) to (32). The solution of equation (42) is shown as follows:…”
Section: Determination Of Parametersmentioning
confidence: 99%